The Effectiveness of Dhuha Prayer Habituation Activities in Shaping Students’ Disciplinary and Religious Character - Anesta Sopiah; Ana Utami Fatoni; Eva Yuliani; Afiani, Siti Linda; Yuliyana, Yuliyana; Dini Astuti; Firda Aulia; Uul Ulfiyah; Siti Hapidoh (The Future of Education Journal, 2026)
This study was conducted to investigate the implementation of character education focused on discipline and religious values at SDIT Bina Bangsa in the city of Serang. The research methodology employed in this study was qualitative and descriptive. Data collection for this study involved observational data, interviews, and documentation, all of which involved teachers and students. The results indicate that performing the Dhuha prayer regularly can enhance students’ disciplinary and religious attitudes. These disciplinary attitudes are demonstrated by students’ adherence to existing rules, fulfillment of their responsibilities, and awareness of the importance of performing religious duties independently. Synergy between the school and parents, supportive school policies, and teacher role modeling contributed to the success of this initiative. Thus, performing the Dhuha prayer can serve as an effective method for instilling a disciplined attitude in elementary school students grounded in Islamic values.